Some problematic questions concerning the disposition of the common property of spouses in Ukrain - Dâkovič, Miroslava (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The article is dedicated to the problematic questions of the disposition of the common property of spouses. The author sheds light on the peculiarities of the disposition of the common property of spouses in the sphere of credit legal relations. Separate attention is paid to the legislative amendment as to the expansion of common ownership regime on the housing, acquired by one of the spouses while being married by way of state housing fund privatization, and plot of land, acquired by way of free of charge transfer to one of the spouses from the state and communal property funds, including privatization. As a result of scientific research, legislation and judicial practice analysis a number of propositions are introduced to improve the procedure of the disposition of the common property of spouses.
Keywords: Ukraina; majatek wspólny małżonków